Synthesis of Carbocycles Using Coinage Metal Catalysis and Formal Synthesis of (±)-Morphine - Brousseau, Julie (Université d'Ottawa / University of Ottawa, 2020)
Coinage metals such as copper, silver and gold have captivated mankind with their desirable qualities and social value. Recently, these metals have peaked the interests of scientists, where organic chemists have used them extensively in the homogenous catalysis of organic transformations. In our laboratory, we exploited their π-Lewis acidic properties to activate alkyne to induce intramolecular cyclization of nucleophilic enol ethers. We discovered that modulating the steric and electronic profiles of the ancillary ligand on the cationic metal complexes allowed for the regioselective control of such reactions. During the exploration of the substrate dependency of these transformations, we discovered that unsubstituted alkynes undergo a 6-endo-dig/acetalization/Prins reaction cascade in the presence of a silver salt such as [(BrettPhos)Ag(MeCN)]SbF6, resulting in the formation of highly strained polycycles. We have demonstrated that the formation of these products is initiated by a selective 6-endo-dig cyclization. Further mechanistic studies suggested that the reaction may occur through silver dual catalysis using deuterium-labelling experiments, however, single activation of the starting material would lead to the same product and thus both mechanisms were proposed. The further reactivity of these interesting polycyclic products was also explored. Total synthesis of natural products is often referred to as an art, as it defines the boundaries of organic chemistry. In our laboratory, we have always been interested in the challenge of ingeniously building architecturally complex molecules. With the development of optimized conditions for the selective formation of decaline cores from silylenol ethers, the application of this methodology to the synthesis of teucrin A was sought. Our synthetic approach is highlighted by a sequential Diels-Alder/6-endo-dig cyclization reaction to rapidly assemble the clerodane diterpenoid framework of the natural product. To that end, the synthesis of the target utilized a strategy featuring a Diels-Alder reaction between an exocyclic allene and a silyl enolether, which proceeded in 59% yield at 110°C with a diasteomer ratio of 3:1. Unfortunately, attempts to induce the [4+2] cycloaddition using Lewis acids that were vital to the proposed synthetic route led to either no conversion or hydrolysis of starting material. Since this key step proved challenging, alternative synthetic pathways are currently being investigated in our group. Since the elucidation of its molecular structure by Robinson in 1925, morphine has received tremendous attention from the synthetic community. Indeed, about 50 formal and total syntheses of morphinans have been reported since the original synthesis by Gate in 1952. Herein, the synthetic efforts achieving a 9-step formal synthesis of (±)-morphine from readily available starting materials such as o-vanillin is presented. This synthesis features the quick assembly of the phenanthrofuran framework of the natural product in only five steps. The tetracyclic intermediate was synthetized through the careful orchestration of a Diels-Alder/elimination/deprotection sequence as well as a telescopic Claisen rearrangement/Friedel-Crafts alkylation. Subsequent strategic functional group manipulations allowed us to reach the advanced compound in four more steps and thus intercepting a known intermediate, which required two additional chemical transformations to form morphine. Overall, the work presented in this thesis represents the development of innovative methods for the creative disconnection of natural products. These advancements promote the rapid assembly of molecular cores found in many bioactive molecules.
Keywords: Synthesis; Catalysis; Coinage Metals; Natural Products